2020
DOI: 10.21203/rs.3.rs-17996/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast recognition of Lecanicillium spp. and its virulence against Frankliniella occidentalis

Abstract: Background: Frankliniella occidentalis (Thysanoptera: Thripidae) is a highly destructive sucking pest of numerous crops. The entomogenous fungi of Lecanicillium spp. are important pathogens of insect pests, and some have been developed as commercial biopesticides. In order to explore the wild resources of Lecanicillium spp. in the development of more effective F. occidentalis controls, efficient gene combinations for strain identification were screened from internal transcribed spacer (ITS) and the genes SSU, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The entomogenous fungi of Lecanicillium spp. are important pathogens of insect pests and can maintain the healthy growth of plants (Zhou et al, 2020). Ramy et al (2020) found that metabolites of Cladosporiumin can effectively inhibit pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The entomogenous fungi of Lecanicillium spp. are important pathogens of insect pests and can maintain the healthy growth of plants (Zhou et al, 2020). Ramy et al (2020) found that metabolites of Cladosporiumin can effectively inhibit pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Charlesworth Group (http://charlesworth.com.cn/) for editing a draft of this manuscript. This manuscript has been released as a pre-print at research square (Zhou et al, 2020).…”
Section: Acknowledgmentsmentioning
confidence: 99%